Fault analysis of HVDC converter based on alternate arm converter topology - Faisal M.; Das J.; Shawon M.; How D.N.T. (Alpha Publishers, 2023)
Recent advancement of High Voltage Direct-Current (HVDC) transmission based on alternate arm converter (AAC) draws the attention of researchers due to their unique structure. It is a hybrid converter as the characteristics of this converter varies among the modular multilevel converter (MMC), due to the existence of H-bridge cells, and the two-level converter, in the sort of director switches in every arm of the converter. AAC presents the improved fault tolerant characteristics compare to traditional voltage source converter (VSC). It has gained much popularity in HVDC transmission because of its robustness against fault, ability of generating superior ac voltage compares to the dc terminal voltage. At this point energy balance between the ac and dc terminal is equal. Therefore, the significant contribution of this paper is to analyze the performance of AAC model under normal condition and fault condition which proves the robustness of AAC converter against the faulty situation. Both AC and DC faults are considered in this study. Simulation is performed in Matlab/ Simulink environment. 2020 Alpha Publishers.